Dextran-conjugated tetrathiatriarylmethyl radicals as biocompatible spin probes for EPR spectroscopy and imaging. Issue 14 (15th July 2019) - Poncelet, Martin; Driesschaert, Benoit; Tseytlin, Oxana; Tseytlin, Mark; Eubank, Timothy D.; Khramtsov, Valery V.
Graphical abstract: Abstract: Tetrathiatriarylmethyl (TAM) radicals represent soluble paramagnetic probes for biomedical electron paramagnetic resonance (EPR)-based spectroscopy and imaging. There is an increasing demand in the development of multifunctional, biocompatible and targeted trityl probes hampered by the difficulties in derivatization of the TAM structure. We proposed a new straightforward synthetic strategy using click chemistry for the covalent conjugation of the TAM radical with a water-soluble biocompatible carrier exemplified here by dextran. A set of dextran-grafted probes varied in the degrees of Finland trityl radical loading and dextran modification by polyethelene glycol has been synthesized. The EPR spectrum of the optimized macromolecular probe exhibits a single narrow line with high sensitivity to oxygen and has advantages over the unbound Finland trityl of being insensitive to interactions with albumin. In vivo EPR imaging of tissue oxygenation performed in breast tumor-bearing mouse using dextran-grafted probe demonstrates its utility for preclinical oximetric applications.